(3hTGM GdOejIs - (3XgjQ GdOjf CHi GdMSf Ydj Hf RjO GdHjgbjs; (3GdHGNQRj , Ydj Hf GdMSf Hf Ydj Hf CHj GdWjH, CHh GdMSf,J (B467 (3g` s
(3ChdgG (B:s
(3HJQLeI fLe GdOjf CHj GdaJhM GdHZOGOi s
(3BNQgG (B:s
(3HJQLeI eMeO Hf GdMSf Hf HfOGQ s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B175 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs